Improving working conditions in response to skills shortages - Tkachenko, Vladyslav; Sereda, Olena H.; Lutsenko Оlena Yе.; Musiienko, Oleg L.; Ivchuk, Yuliia Yu. (European Public & Social Innovation Review, 2025)
Introduction: The article is devoted to the study of ways to improve working conditions as a response to the shortage of qualified personnel in the modern labor market. Methodology: To conduct a thorough study of improving working conditions in situations where there is a shortage of skilled personnel, the methodology of this study includes analysis, synthesis, induction, deduction, dialectical, analytical, analogical, and generalizable methods Results: The results provide an overview of EU regulations on occupational safety and working time, as well as examples of effective practices for improving working conditions at the enterprise and state levels. Discussions: The article focuses on the role of legislative initiatives in European countries (Sweden, the Netherlands, Germany, Finland, France, Great Britain), which have proven the effectiveness of reducing working hours, strengthening social guarantees and supporting lifelong learning. Conclusions: The findings emphasize that the modernization of working conditions is a strategic factor in increasing productivity, reducing staff turnover, and long-term business competitiveness, and also identify areas for further research on the impact of different models of work organization and social protection on labor market stability.